Improving the Marketing Approach in Managing Export-Oriented Distribution Channels - Usmonova Dilfuza Ilkhomovna; Tursunov Ozod (Research Parks Publishing LLC, 2021)
This article discusses the ways of developing the distribution activities of domestic producers in foreign markets. The features of the formation of the distribution policy using the marketing approach in management are revealed.